2006
DOI: 10.21000/jasmr06022585
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Evapotranspiration Cover Systems at Barrick Goldstrike Mines

Abstract: Barrick Goldstrike Mines Inc. (BGMI) has developed a comprehensive closure planning, materials characterization and in-situ monitoring program for the closure of its mine waste facilities. Facility closure techniques use topsoil and in-pit material to construct evapotranspiration (ET) cover systems to reduce or eliminate infiltration of meteoric water. One major facility at BGMI, the AA Leach Pad (AA Pad) has been closed. The Bazza Waste Rock Facility (WRF), which will hold about 1.75 billion metric tonnes (mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…These calculations have been complemented by laboratory experiments (Bussière et al 1998) and validated using monitoring data obtained from in situ cover systems (e.g. Bussière 1999; Bussière et al 2003a;Zhan et al 2001aZhan et al , 2006. The results obtained through these studies have shown that the behavior of inclined CCBEs is intrinsically dynamic.…”
Section: Transient Effectsmentioning
confidence: 93%
See 2 more Smart Citations
“…These calculations have been complemented by laboratory experiments (Bussière et al 1998) and validated using monitoring data obtained from in situ cover systems (e.g. Bussière 1999; Bussière et al 2003a;Zhan et al 2001aZhan et al , 2006. The results obtained through these studies have shown that the behavior of inclined CCBEs is intrinsically dynamic.…”
Section: Transient Effectsmentioning
confidence: 93%
“…Stormont 1996;Bussière et al 1998;Morris and Stormont 1998;Kämpf et al 2003;Tami et al 2004) and more representative simulations that better reflect the actual field behavior of covers (e.g. Zhan et al 2001aZhan et al , 2006Bussière et al 2003a). …”
Section: Limitations Of Ross's Solution and Comparison With Other Anamentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of CCBEs has been assessed in the laboratory (Bussière et al , 1998Kämpf and Montenegro 1997;Stormont and Anderson 1999;Kämpf et al 2003;Tidwell et al 2003;Yang et al 2004), in the field (Stormont 1995a;Stormont et al 1996;Aubertin et al 1997;Barth and Wohnlich 1999;von Der Hude et al 1999;Cabral et al 2007), as well as by numerical simulations (Akindunni et al 1991;Oldenburg and Pruess 1993;Bussière et al 1995Bussière et al , 2003Kämpf and Montenegro 1997;Webb 1997;Morris and Stormont 1999;Khire et al 2000;Zhan et al 2001Zhan et al , 2006Aubertin et al 2006Aubertin et al , 2009Cifuentes et al 2006).…”
Section: Basic Principles Of Capillary Barriers (Cb)mentioning
confidence: 99%
“…An ET cover is a selfrenewing biological system and is expected to last much longer than the conventional compacted clay barrier. ET covers have been used above landfills (e.g., Albright et al, 2004;Apiwantragoon et al, 2015;Barnswell and Dwyer, 2011;Benson et al, 2001;Benson et al, 2007;Santini and Fey, 2014;Scanlon et al, 2005), waste sites (e.g., Bowerman and Redente, 1998;Gee et al, 1997;Link et al, 1995;Pettit et al, 1994;Rutqvist et al, 2011;Scanlon et al, 1997;Waugh et al, 2010;Waugh et al, 2007;Wing and Gee, 1994;Zhang, 2015), and mine lands (e.g., Barber et al, 2015;Meiers et al, 2015;O'Kane and Wels, 2003;Zhan et al, 2006). The function of an ET cover is to protect the underlying materials, provide a medium for vegetation growth, store precipitation within the cover, and release the stored precipitation later into the atmosphere so that the infiltration of precipitation waste zone is minimized.…”
Section: Introductionmentioning
confidence: 99%